2021
DOI: 10.3389/fonc.2020.596448
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Inversion Time for FLAIR Acquisition on the T2-FLAIR Mismatch Detectability for IDH-Mutant, Non-CODEL Astrocytomas

Abstract: The current research tested the hypothesis that inversion time (TI) shorter than 2,400 ms under 3T for FLAIR can improve the diagnostic accuracy of the T2-FLAIR mismatch sign for identifying IDHmt, non-CODEL astrocytomas. We prepared three different cohorts; 94 MRI from 76 IDHmt, non-CODEL Lower-grade gliomas (LrGGs), 33 MRI from 31 LrGG under the restriction of FLAIR being acquired with TI < 2,400 ms for 3T or 2,016 ms for 1.5T, and 112 MRI from 112 patients from the TCIA/TCGA dataset for LrGG. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…There have been great efforts within the research community to develop noninvasive imaging techniques that can predict IDH mutation status in gliomas, including magnetic resonance spectroscopy (MRS) 6 8 , perfusion- and diffusion-weighted magnetic resonance imaging (MRI) 9 , 10 , and machine learning with conventional MRI 5 , 11 , 12 . Whereas these techniques rely mainly on quantitative or semi-quantitative MRI measurement, qualitative imaging features such as the “T2 fluid-attenuated inversion recovery (FLAIR) mismatch sign” have proven to be powerful imaging surrogate markers for predicting IDH mutation status in tumors that appear to be histologically LrGGs 13 15 . These qualitative imaging features are derived from radiologically quantitative measurements such as the T1- and T2-relaxation time 15 , 16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been great efforts within the research community to develop noninvasive imaging techniques that can predict IDH mutation status in gliomas, including magnetic resonance spectroscopy (MRS) 6 8 , perfusion- and diffusion-weighted magnetic resonance imaging (MRI) 9 , 10 , and machine learning with conventional MRI 5 , 11 , 12 . Whereas these techniques rely mainly on quantitative or semi-quantitative MRI measurement, qualitative imaging features such as the “T2 fluid-attenuated inversion recovery (FLAIR) mismatch sign” have proven to be powerful imaging surrogate markers for predicting IDH mutation status in tumors that appear to be histologically LrGGs 13 15 . These qualitative imaging features are derived from radiologically quantitative measurements such as the T1- and T2-relaxation time 15 , 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Whereas these techniques rely mainly on quantitative or semi-quantitative MRI measurement, qualitative imaging features such as the “T2 fluid-attenuated inversion recovery (FLAIR) mismatch sign” have proven to be powerful imaging surrogate markers for predicting IDH mutation status in tumors that appear to be histologically LrGGs 13 15 . These qualitative imaging features are derived from radiologically quantitative measurements such as the T1- and T2-relaxation time 15 , 16 . Ideally, tissue relaxation time should be directly measured by MR relaxometry; however, this has not yet been incorporated into routine imaging protocols as it requires additional scan time.…”
Section: Introductionmentioning
confidence: 99%
“… 8 Kinoshita et al suggested that IDH -mutant, non-codeleted astrocytomas often contain tumors that exhibit long T1 and T2 effects, which phenomenon could be the leading cause of the T2-FLAIR mismatch sign. 9 In our case, histological features include the diffuse proliferation of glioma cells with no microcystic changes but edematous changes in the background. Taken together, the T2-FLAIR mismatch sign would represent histological features themselves than genetic profiles.…”
Section: Discussionmentioning
confidence: 60%
“…We tested this hypothesis by investigating the image acquisition parameters of the TCIA dataset and found that differences in inversion time played a critical role in the presence or absence of the T2-FLAIR mismatch sign for astrocytoma with IDH mutation. 91) AUROC increased from 0.63 to 0.87 if the inversion time was correctly adjusted for FLAIR acquisition aiming at glioma imaging ( Fig. 5 ).…”
Section: Quantitative Analysis Of the T2-flair Mismatch Sign And Reverse Engineering It To Conventional Neuroimagingmentioning
confidence: 99%
“…Both cases highlight the importance of TI for FLAIR acquisition in terms of visualization of the T2-FLAIR mismatch sign. The figure was cited from Kinoshita et al 91) with minor modification under the terms of the Creative Commons Attribution License (CC BY).…”
Section: Figmentioning
confidence: 99%